Large Area Three‐Dimensional Photonic Crystal Membranes: Single‐Run Fabrication and Applications with Embedded Planar Defects. Issue 2 (3rd December 2018) - Chang, Bingdong; Zhou, Chen; Tarekegne, Abebe Tilahun; Yang, Yuanqing; Zhao, Ding; Jensen, Flemming; Hübner, Jörg; Jansen, Henri
Abstract: Three‐dimensional photonic crystals (3D PhCs) enable light manipulations in all three spatial dimensions, however, real world applications are still faced with challenges in fabrication. Here, a facile fabrication strategy for 3D silicon PhCs with a simple cubic (SC) lattice structure is presented, which exhibits a complete photonic bandgap at near‐infrared wavelengths of around 1100 nm. The fabrication process is composed of standard deep ultra‐violet stepper lithography, followed by a single‐run modified plasma etch process. By applying a direct dry etch release step at the end of the 3D structural etch process, the fabricated 3D PhCs can be released and transferred in the form of a membrane onto other substrates such as glass, polymers, or even substrates with engineered surface. The thickness of the demonstrated membranes is around 2 µm and the size can be up to a few millimeters. A high reflectivity is observed at the stop band frequency, and a planar defect is introduced during the etching process resulting in an optical resonance mode with a small linewidth of around 30 nm. The structure constitutes an optical bandpass filter and can be used as a sensor for organic solvents. Abstract : Large area three‐dimensional photonic crystal membranes are fabricated conveniently with DREM (deposit, remove, etch, multistep) plasma etch process. The fabricated membranes have excellent mechanical properties and can be transferred to other substrates or be infiltrated by polymer. Planar cavities can be embedded on purpose into the membranes for applications such as solvent sensor or bandpass filters.